Investigation of the layout of kilowatt-scale wind turbines located among megawatt-scale ones by means of an analytical model - Peyman Asad Ayoubi; Mohammad Eftekhari Yazdi; Iraj Harsini (مجله مدل سازی در مهندسی, 2022)
The methods used for maximum exploitation of wind farms’ potentials can be classified into two categories: turbines layout optimization and utilization of turbines with different hub heights. The layout optimizations are generally performed by optimization algorithms. A drawback of these algorithms is their inability to render a single result as the optimized result. In the present study, by using an analytical model for 3D wind velocity distribution in the wake and including wake interactions, a model has been presented for estimation of the generated power of turbines implemented in wind farms. By coupling this model with the cost model of turbines' implementation, a function for the optimized layout has been presented. By calculating this function for different layouts of turbines in farms, the optimized layout can be obtained. In the present study, the calculations of turbines' layout optimization were carried out using a MATLAB-implemented code. By dividing the solution domain into grids and taking into account the minimum optimized distance of turbines from one another from the economical and power output aspects, the value of the layout optimization function has been calculated for different possible layouts. Finally, the layout of kilowatt-scaled turbines located among megawatt-scale ones for Horns Rev offshore farm has been modeled to obtain the maximum power output. From the results obtained for the optimized and maximum number of kilowatt-scaled turbines, it is inferred that the power of the farm has been increased by 7% (3.226 MW) by 35.7% efficiency and 9.35% (4.712 MW) by 34.06% efficiency,respectively.